2017
DOI: 10.1136/bmjopen-2017-015831
|View full text |Cite
|
Sign up to set email alerts
|

Early detection of perceived risk among users of a UK travel health website compared with internet search activity and media coverage during the 2015–2016 Zika virus outbreak: an observational study

Abstract: ObjectivesThe Zika virus (ZIKV) outbreak in the Americas in 2015–2016 posed a novel global threat due to the association with congenital malformations and its rapid spread. Timely information about the spread of the disease was paramount to public health bodies issuing travel advisories. This paper looks at the online interaction with a national travel health website during the outbreak and compares this to trends in internet searches and news media output.MethodsTime trends were created for weekly views of ZI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…Moreover, consumer avoidance of crisis news might lessen the negative impact of the coronavirus on travel decisions, thus benefitting travel firms. Negative impacts on travel have been evidenced during multiple traumatic events, such as Ebola (Petersen et al , 2017), COVID-19 (Bae and Chang, 2020); and terrorist attacks (Stepchenkova et al , 2019).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, consumer avoidance of crisis news might lessen the negative impact of the coronavirus on travel decisions, thus benefitting travel firms. Negative impacts on travel have been evidenced during multiple traumatic events, such as Ebola (Petersen et al , 2017), COVID-19 (Bae and Chang, 2020); and terrorist attacks (Stepchenkova et al , 2019).…”
Section: Discussionmentioning
confidence: 99%
“…In the case of COVID-19, it is probable that prior travel experience may not be deemed as useful as external sources, since experience with the precise dilemma of traveling during this major pandemic is unknown for most consumers. Consumers rely on search engines and expert travel websites to prepare themselves (Petersen et al , 2017). Travelers who want to travel internationally rely heavily on Internet searches (Pesonen and Pasanen, 2017).…”
Section: Background Literaturementioning
confidence: 99%
“…Google has been used to monitor Ebola-related web search behaviour and dengue outbreaks. [20][21][22] Some authors have used a travel health website 23 to monitor anxiety over the Zika virus, others have examined the framing of the Zika crisis 24 in two Brazilian newspapers (O Globo and Folha de Sao Paulo) and the coverage of mosquito-borne diseases in Italian newspapers 25 and compared Zika with other diseases.…”
Section: Mass Media and Public Health Informaticsmentioning
confidence: 99%
“…The February and August peaks are also similar, coinciding with visits to a UK travel health website. 23 In addition, as will be shown in the next section, newspapers provide information on the scientific and non-scientific discourses about disease, public perceptions and how these may have influenced the uptake of containment information.…”
Section: Research Question 11mentioning
confidence: 99%
“…Studies have shown that the decision to visit a destination involves a reasoned cost–benefit analysis based on information taken from various sources ( Abubakar and Ilkan, 2016 ; Chen et al, 2014 ). Moreover, a 2017 study showed that perceived risk preceded increased user traffic on a travel health website ( Petersen et al, 2017 ). Thus, reading travel health information about COVID-19 on travel websites and from official sources such as government public health and industry platforms may influence travel decision-making ( Huang et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%